Tytuł Boga RḤMNN – "Miłosierny" z żydowskich i chrześcijańskich inskrypcji przedmuzułmańskiej Arabii. Politeistyczna czy monoteistyczna geneza koranicznego ar-Raḥmān? - Kościelniak, Krzysztof (Analecta Cracoviensia, 2011)
Recited several times as part of the Muslim daily prayers basiamo contains three definite nouns: Allah, Raḥmān and Raḥmīm ([…]; bismi-llāhi r-raḥmāni r-raḥīm). Especially the epithet […] ( Raḥmān - "the Merciful"), which is found in the Sabaean inscriptions in the form RḤMNN (Raḥmānān), has a relatively long history in the Middle East. The study of the pre-Islamic Arabic cultures provides the context of numerous religious interactions in the evolution of Raḥmān's meaning. RḤMNN - used by Polytheist Arabs, Jews and Christians - is constantly confirmed in inscriptions, particularly from the so-called "Late Sabaean Period" (after 380) that were associated with Monotheism. During that time Judaism and Christianity attempted to replace the traditional South Arabian religion. Muhammad might have borrowed this name from three sources, which were present in his milieu. RḤMNN - [...] understood by Jews and Christians as "Lord, the Merciful, Master of Heaven" was useful for Islam, the new Monotheistic religion. On the other hand, in South Arabia RḤMNN signified a Moon-god, whom Muhammad even occasionally confused with "Allah" or used as a substitute for "Allah".